Model Intensi Berwirausaha Pada Mahasiswa Fakultas Dakwah Dan Komunikasi Universitas Islam Negeri Sumatera Utara - Cut Metia; elfi yanti ritonga; Mutiawati Mutiawati (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
This research is motivated by the high unemployment rate for students who have completed education at the college level. This study uses a quantitative research approach with a type of path analysis. The location of the research that will be conducted is the Dakwan Faculty and UIN North Sumatra Medan Communication students. The data to be collected in this study are Likert scale data about self efficacy, Career Maturity, Social Support, and Entrepreneurial Intention. Data analysis techniques are based on descriptive analysis and analysis of structural equations, especially path analysis. The results of the study revealed that the theoretical model of entrepreneurial intention is fit with its empirical data, only the self efficacy and career maturity variables directly influence entrepreneurial intention in student samples.